2019
DOI: 10.3390/plants8100403
|View full text |Cite
|
Sign up to set email alerts
|

Nitric Oxide Enhances Cytotoxicity of Lead by Modulating the Generation of Reactive Oxygen Species and Is Involved in the Regulation of Pb2+ and Ca2+ Fluxes in Tobacco BY-2 Cells

Abstract: Lead is a heavy metal known to be toxic to both animals and plants. Nitric oxide (NO) was reported to participate in plant responses to different heavy metal stresses. In this study, we analyzed the function of exogenous and endogenous NO in Pb-induced toxicity in tobacco BY-2 cells, focusing on the role of NO in the generation of reactive oxygen species (ROS) as well as Pb2+ and Ca2+ fluxes using non-invasive micro-test technology (NMT). Pb treatment induced BY-2 cell death and rapid NO and ROS generation, wh… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
6
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(6 citation statements)
references
References 54 publications
0
6
0
Order By: Relevance
“…Similarly, nitrosative and oxidative stresses were reported under alkalinity and/or aniline stresses (Dawood et al 2021b), collectively known as secondary stress, i.e., "nitro-oxidative stress" (Corpas and Barroso 2013). Thus, herein, NO could be a potential agent in Hg-mediated ROS production and, subsequently, oxidative perturbations, as recommended by the study of Wu et al (2019). Contrary to this, the application of algal extracts vastly reduced both ROS and NO; consequently, high tolerance to Hg stress was the result.…”
Section: Discussionmentioning
confidence: 78%
“…Similarly, nitrosative and oxidative stresses were reported under alkalinity and/or aniline stresses (Dawood et al 2021b), collectively known as secondary stress, i.e., "nitro-oxidative stress" (Corpas and Barroso 2013). Thus, herein, NO could be a potential agent in Hg-mediated ROS production and, subsequently, oxidative perturbations, as recommended by the study of Wu et al (2019). Contrary to this, the application of algal extracts vastly reduced both ROS and NO; consequently, high tolerance to Hg stress was the result.…”
Section: Discussionmentioning
confidence: 78%
“…It is reported that the expression of Ca 2+ /Mg 2+ -dependent nucleases causes DNA fragmentation in the nucleus and other forms of apoptosis [ 57 ]. Moreover, studies have shown that changes in intracellular Ca 2+ homeostasis can lead to the release of cytochrome c, which triggers PCD [ 58 , 59 ]. So, ET signaling can activate downstream Ca 2+ signal-related genes to increase cytoplasmic Ca 2+ , which leads to the expression of PCD-associated genes, thereby also promoting PCD in pir1 .…”
Section: Discussionmentioning
confidence: 99%
“…Several biochemical indicators are useful tools to distinguish PCD from necrosis. A very common indicator of PCD in plant cells is the internucleosomal fragmentation of DNA, which is easily determined by the TUNEL assay that labels 3′-OH ends produced as a result of DNA fragmentation [ 18 , 71 , 90 , 91 ]. The early stage of PCD could be detected using a very fast and cost-effective DNA ladder assay, where specific endonucleases attack nuclear DNA, producing double-stranded DNA fragments with low molecular weights [ 92 ].…”
Section: Plant Cell Death Under Abiotic Stress—pcd Vs Necrosismentioning
confidence: 99%
“…Ethylene, the level of which is modulated by ROS formation and stimulates the redistribution of Ca 2+ , also participates in the onset of PCD [ 5 , 7 ]. The cellular response to Cd and Pb involves complex crosstalk between ROS, hormones (ethylene), NO, and Ca 2+ [ 6 , 91 , 145 ]. Accordingly, NO modulates the content of phytochelatins (PCs), whose function is to bind heavy metals in the cytoplasm and to mediate their vacuolar sequestration [ 102 ].…”
Section: The Physiological Characteristics Of Pcd In Plant Cells Umentioning
confidence: 99%
See 1 more Smart Citation